Interaction of diabetogenic chelat active chemicals with Zn+2-ions in pancreatic B-cells and its role for developing of death of pancreatic B-cells - Meyramov, G.G.; Kikimbaeva, A.A.; Aitkulov, A.M.; Zhuzbaeva, G.O.; Kovalenko, O.L.; Andreewa, A.P.; Meyramova, A.G. (Изд-во КарГУ, 2013)
Authors showed that interaction of diabetogenic chelators as Diphenylthiocarbazone and formed in Human some derivatives of 8-oxyquinolin with Zn2+-ions contained in B-cells result destruction of cells and develop- ing of 1 type diabetes. Preliminary elimination of Zn2+ — ion- from cells or blocking ions by not diabetogenic chelators protect B-cells of interaction with diabetogenic substances and as result — of developing of diabetes.
Keywords: Diabetes; Diphenylthiocarbazone (Dithizon); B-cells; fluorescence; Human; Rabbits; Histochemical results; Revealing; Destruction